Orthorexia nervosa: Healthy habit or pathology? Experiences and expansion of the consciousness of the correct diet - Ginés Mateo-Martínez; Antonio Vázquez-Sellán; María Luisa Díaz-Martínez; María Carmen Sellán-Soto (Heliyon)
Aim: Exploring the lived experience of women concerned about following a healthy and sustainable diet: subjectivity, ideas, descriptive concepts, and constitutive strategies. Method: Based on the epistemological paradigm of phenomenology, the theoretical perspective of symbolic interactionism, and the methodological perspective of phenomenological reduction, a qualitative discourse analysis was performed through different strategies (thematic content analysis and interpretive phenomenological analysis, applying ad hoc techniques). Findings: The phenomenological field of healthy eating intermittently unfolds in both experience and discourse, akin to a process of expansion and contraction, in the narrative “Expanding the Consciousness of Healthy Eating”. This encompasses two main themes: (1) Researching and Gathering Information, with the subthemes ‘Health Socialisation,’ ‘My Purchase: Assessing Food Reliability,’ ‘Moral Burden,’ and ‘Compensation as a Mechanism of Channelling Deviation’; and (2) Becoming Healthier, with the subthemes ‘Highlighting Benefits,’ ‘Marketing as a Pandemic Resource of Ideals,’ and ‘Is the Clinical Eye of the Family a Stigmatising Label?'. Conclusion: The process of becoming healthier entails a struggle with the environment and with one's inner self. This struggle is open to the entire world and guided by the unalienable tenets of health, respectfulness, goodness, and beauty as ‘the only alternative’ to the suffering caused by a conventional diet.